Indigenous peoples, their rights and customary laws in the North: the case of the Sámi people - Dawid Bunikowski (The Geographical Society of Northern Finland, 2014)
The paper focuses on indigenous peoples, their rights and customary laws in the North in context of the Sámi people situation in the Nordic countries and Russia. It is to analyse and conceptualise some important issues concerning Sámi customary laws in the light of indigenous rights, constitutional law and legal pluralism as well as to propose new forms of cooperation between universities or scholars in the North in research in this field. First, after proposing new forms of academic cooperation, we flash focus on theory of legal pluralism and on Sámi customary laws. Secondly, we differ the institutional axiology from the real axiology in state legal orders. Thirdly, we analyse rules concerning the Sámi in Finland’s legislation, Sweden’s constitutional acts and Norway’s Constitution. Fourthly, we express some chosen conflicts of laws: Sámi laws versus national laws and interests. Fifthly, using many criteria, we try to evaluate the Nordic countries in the field of recognition of indigenous rights. Sixthly, we show Russia’s laws and Sámi problems (the Ponoi case and violation of the Russian Sámi rights). Seventhly, we consider contemporary problems of Sámi: the right of indigenous peoples to customary law, the right to self-determination as a basis of Sámi claims, and finally, treating Sámi as “people”, “nation”, not “ethnic minority”. I also analyse what was behind the current state of affairs in Scandinavia, proposing a classification of political, ideological, religious and educational, economic, and cultural factors. In the conclusion, I maintain that indigenous rights, including Sámi rights to land and political self-government, should be better recognised in the North. It still remains a paradox, as the problem is not resolved in Scandinavian liberal societies, which are supposed to be sensitive in the field of human rights and protection of cultural diversity. I think that going back to customary laws or legal pluralism is such an inspiration for seeking new forms of political organisation of the Sámi ...